All for One: The Role of Colony Morphology in Bryophyte Desiccation Tolerance - Cruz de Carvalho, Ricardo; Maurício, António; Pereira, Manuel Franscisco; Marques da Silva, Jorge; Branquinho, Cristina (Frontiers in Plant Science, 2019)
In the last decade, several works showed that even bryophytes from aquatic environments, if slowly dehydrated, can cope with desiccation in a response like the one from desert bryophytes. This led to the hypothesis that, if bryophytes from contrasting habitats can have similar responses, desiccation tolerance (DT) is partially inductive and not only constitutive as previously proposed and, therefore, colony morphology might be the key trait responsible for controlling dehydration rate essential for DT induction. Morphology and life form may be determinant traits in the adaptation of bryophytes to habitats with different water availabilities and corresponding predicted levels in the DT inducibility spectrum. Bryophytes from habitats with different water availabilities were dried as individual shoots and as a colony. The bryophyte Fontinalis antipyretica is fully aquatic presenting a streamer life form, while the three terrestrial species present turf life form with different sizes and degrees of space between individuals in the colony. Two species were collected under trees with moist soil presenting short turf (Tortella tortuosa) and long turf (Campylopus pyriformis) life forms. Another species was completely exposed to sun light with no surrounding trees and a tall turf life form (Pleurochaete squarrosa). We used chlorophyll a fluorescence parameter Fv/Fm (maximum potential quantum efficiency of Photosystem II) as a proxy to photosynthetic fitness throughout the contrasting dehydration rates (fast and slow). These bryophytes with different life forms were submitted to an X-ray computed microtomography (μ-XCT) to assess the three-dimensional inner structure and visualize locations for water storage. Shoots dried slow or fast according to the dehydration they were exposed to, as expected, but they presented similar dehydration rates across different species. However, the aquatic moss F. antipyretica, was unable to recover from fast drying, and after 24 hours the recovery following slow drying was lower than the other species. The other three species presented full recovery after 24 hours, either at the individual or colony level, and either from slow or fast drying. The only exception was the colonies of Campylopus pyriformis following fast drying that presented a slightly lower recovery, probably due to a looser colony structure.